The Correlation Between Cobb’s Angle and Pedicle Rotation in Adolescent Idiopathic Scoliosis After Surgical Treatment - Danu Purnama Aji; Hermina Sukmaningtyas; Agus Priambodo; Christina Hari Nawangsih (Faculty of Medicine, Diponegoro University, 2021)
Background: Adolescent Idiopathic Scoliosis (AIS) is a 3-dimensional deformity that involves not only curve in the coronal and sagittal planes but also rotation of vertebrae based on pedicle rotation. The Cobb’s angle is the gold standard for measuring the lateral curve that could show severity of the spine deformity. The Cobb’s method only evaluate the lateral curve,and the method to determine the pedicle rotation can be used the Nash and Moe’s method.The higher pedicle rotation grade had higher Cobb’s angle. Surgical treatment for scoliosis is indicated for the curve exceeding 40o. Posterior spinal fusion is the most commonly used technique in scoliosis surgery.Objective: To identify the correlation between the Cobb’s Angle and pedicle rotation in AIS after surgical treatment.Methods: The research design used in this study was Cross Sectional. The sample size of this study were 22 subjects using purposive sampling, the independent variable of this study was Cobb’s angle while the dependent variable was pedicle rotation. Spearman’s rank correlation was used to analyze the correlation between variable.Results: The spearman’s rank correlation revealed a significant correlation between the Cobb’s Angle and pedicle rotation in AIS after surgical treatment with the p 0,005 and r 0,462.Conclusion: This study demonstrates there is a significant correlation between Cobb’s angle and pedicle rotation in AIS after surgical treatment with medium strength.